Comparative Evaluation of Effectiveness of Rocuronium Bromide vs. Succinyl Choline on Quality of Intubating Conditions during General Anesthesia - Burkul, Aditi; Memon, Nazima; Kulkarni, Vaishnavi (International Journal of Integrated Health Sciences, 2023)
Objectives: To compare the quality of intubating conditions and hemodynamic responses to the administration of Rocuronium Bromide and Succinyl Choline during general anesthesia.Methods: This was a comparative study conducted at the anesthesiology department of a tertiary care medical college. Sixty patients undergoing various surgeries under general anesthesia were included in this study based on predefined inclusion and exclusion criteria. Patients were divided into Group S (receiving succinylcholine) and Group R (receiving rocuronium). In all patients, the quality of intubating conditions was assessed. Excellent or good conditions were considered to be acceptable intubating conditions, whereas fair and poor conditions were considered unacceptable.Results: Mean age, weight, gender distribution, and ASA grades were comparable in both groups. The overall quality of intubation was found to be better in group S than in group R, and the difference was statistically significant (P=0.004). The duration of action was significantly longer in group R than in group S (P<0.001). Hemodynamic stability was comparable in both the groups, except for heart rate at 10 min, which was higher in Group R than in Group S. Incidence of fasciculation was significantly more in Group S as compared to Group R, and the difference was found to be highly significant (P=0.0001).Conclusion: Succinylcholine for rapid sequence intubation is associated with better intubation conditions than rocuronium.